asp46
contestada

f(x)= 2x+3/x-1, x ≠ 1, dan f^-1 adalah invers dari f
tentukan :
A. infers fungsi F
B. Nilai dari f^-1 (-3)​​

Respuesta :

Answer:

The answer are

A.

[tex] {f}^{ - 1} (x) = \frac{x + 3}{x - 2} [/tex]

B.

[tex] {f}^{ - 1} ( - 3) = 0[/tex]

Step-by-step explanation:

To find the infers we do that

[tex]f(x) = \frac{2 x + 3}{x - 1 } \\ (x - 1)f(x) = 2x + 3 \\ xf(x) - f(x) = 2x + 3 \\ xf(x) - 2x = f(x) + 3 \\ x(f(x) - 2) = f(x) + 3 \\ x = \frac{f(x) + 3}{f(x) - 2} \\ then \: \\ {f}^{ - 1} (x) = \frac{x + 3}{x - 2} \\ then \\ {f }^{ - 1} ( - 3) = \frac{ - 3 + 3}{ - 3 + 2} = 0[/tex]